Metabolomics Reveals Distinct Metabolites between Lonicera japonica and Lonicera macranthoides Based on GC-MS - Rui-ying Liu; Jing Deng; Xiu-Lian Lin; Ya-mei Li; Yan Lin; Bo-hou Xia; Li-mei Lin (Journal of Chemistry)
Lonicera japonica Thunb. (LJ) and Lonicera macranthoides Hand. -Mazz. (LM) have been widely used in Chinese medicine for thousands of years. Although the morphological characteristics of LJ and LM are quite similar, there are significant distinctions of medicinal ingredients (mainly the secondary metabolites) and clinical indications between them. However, the in-depth differences of primary metabolites have not thoroughly been studied yet. Therefore, gas chromatography-mass spectrometry- (GC-MS-) based metabolomics method combined with chemometric methods were performed to analyze the distinction in this study. The results showed that LJ and LM were obviously classified into two groups. 10 metabolites were obtained as biomarkers on account of their p values, pcorr values, and differing variable importance in projection (VIP) values. Metabolic pathway analysis showed that the galactose metabolism and starch and sucrose metabolism gathered as potential pathways caused these extraordinary differences of primary metabolites between LJ and LM. Further, we found that the differences of main medicinal ingredients between LJ and LM could be interpreted from these metabolites according to the analysis of mainly related pathways. The metabolites involved in the starch and sucrose metabolism presented upregulated in LJ, while almost all metabolites in the galactose metabolism, the TCA cycle, and the phenolic acid part of phenylpropanoid metabolism were downregulated in LJ. Therefore, the energy stored in the starch and sucrose metabolism may be saved to produce flavonoid, which could be the reason that the level of flavonoid of phenylpropanoid metabolism is higher in LJ compared to LM. Consequently, this study presented an effective tool for quality evaluation of LJ and LM and laid a foundation for further studies of the metabolic mechanisms and high-quality manufacturing of them.